Bacterial-induced protection against allergic inflammation through a multicomponent immunoregulatory mechanism. Issue 9 (21st March 2011) - Nembrini, Chiara; Sichelstiel, Anke; Kisielow, Jan; Kurrer, Michael; Kopf, Manfred; Marsland, Benjamin J
Abstract : Background: Airborne microbial products have been reported to promote immune responses that suppress asthma, yet how these beneficial effects take place remains controversial and poorly understood. Methods: We exposed mice to the bacterium Escherichia coli and subsequently induced allergic airway inflammation through sensitization and intranasal challenge with ovalbumin. Results: Pulmonary exposure to the bacterium Escherichia coli leads to a suppression of allergic airway inflammation. This immune modulation was neither mediated by the induction of a T helper 1 (Th1) response nor regulatory T cells; however, it was dependent on Toll-like receptor 4 (TLR4) but did not involve TLR desensitisation. Dendritic cell migration to the draining lymph nodes and activation of T cells was unaffected by prior exposure to E.coli, while dendritic cells in the lung displayed a less activated phenotype and had impaired antigen presentation capacity. Consequently, in situ Th2 cytokine production was abrogated. The suppression of airway hyper-responsiveness was mediated through the recruitment of gd T cells; however, the suppression of dendritic cells and T cells was mediated through a distinct mechanism that could not be overcome by the local administration of activated dendritic cells, or by the in vivo administration of tumour necrosis factor a. Conclusion: Our data reveal a localized immunoregulatory pathway that acts to protect the airways from allergic inflammation.